Registro de la tortuga caná (Dermochelys coriacea) en el Parque Nacional Natural Gorgona, Pacífico colombiano (2016)
Leatherback turtle, Dermochelys coriacea is the only species within the Dermochelyidae family. It is the species of marine turtle with the widest geographic distribution, it being in all oceans of the world except Antarctic Ocean. In Colombia it has been frequently reported in the Atlantic where even important breeding beaches and transit zones has been recognized. However, for the Colombian Pacific the information is limited, because the observations of individuals are anecdotal and its presence has only been reported at El Valle – Utría Cove, Chocó. In this document the presence of one adult of D. coriacea is reported at the marine protected area of the Gorgona Natural National Park (Cauca department), 350 kilometers to the south of Utría Cove.